Some Problems of Legal Regulation of Employer’s Labor Legal Personality as a Party to Contract - S. V. Vereitin (Bulletin of Kharkiv National University of Internal Affairs)
Scientific approaches to determining the employer’s labor legal personality within labor legal relations have been studied. The norms of the Labor Code of Ukraine and the drafts of the Labor Code of Ukraine in regard to labor legal personality of the corporate employer and the employer being an individual have been researched. It has been found out that the current Code of Labor Laws of Ukraine does not clearly define the moment of emergence of labor legal personality of the employer. Besides, labor law uses different terms to denote this aspect of the contract. It has been recommended to change all synonyms of the term of “employer” for the specified term in all acts of national legislation.